Analysis of Passing Skills Using the Inside of the Foot in Football Games of Al Amin Pakis Middle School Students - Saputra, Angga; Sudarsono, Sudarsono; Sucipto, Adi; Irawan, Dedy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to determine the ability of passing skills using the inside of the foot in football games in Al Amin Pakis Middle School students. The subjects of this study were 40 8th grade students of Al Amin Pakis Middle School. This study is a quantitative descriptive study, the research method is a survey method with data collection techniques using tests and measurements. The data obtained are in the form of test results and measurements of passing skills using the inside of the foot in football games in Al Amin Pakis Middle School students. It can be concluded that the passing skills using the inside of the foot in football games in Al Amin Pakis Middle School students are in the sufficient category for 32 students or 80%, the less category for 4 students or 10%, and the very less category for 4 students or 10%.